Polymyalgia rheumatica and giant cell arteritis following COVID-19 vaccination: Results from a nationwide survey - Pierre-André Jarrot; Adrien Mirouse; Sébastien Ottaviani; Simon Cadiou; Jean-Hugues Salmon; Eric Liozon; Simon Parreau; Martin Michaud; Benjamin Terrier; Pierre-Edouard Gavand; Ludovic Trefond; Virginie Lavoiepierre; et al. (Taylor & Francis Group, 2024)
ABSTRACTWe conducted a national in-depth analysis including pharmacovigilance reports and clinical study to assess the reporting rate (RR) and to determine the clinical profile of polymyalgia rheumatica (PMR) and giant cell arteritis (GCA) in COVID-19-vaccinated individuals. First, based on the French pharmacovigilance database, we estimated the RR of PMR and GCA cases in individuals aged over 50 who developed their initial symptoms within one month of receiving the BNT162b2 mRNA, mRNA-1273, ChAdOx1 nCoV-19, and Ad26.COV2.S vaccines. We then conducted a nationwide survey to gather clinical profiles, therapeutic management, and follow-up data from individuals registered in the pharmacovigilance study. A total of 70 854 684 COVID-19 vaccine doses were administered to 25 260 485 adults, among which, 179 cases of PMR (RR 7. 1 cases/1 000 000 persons) and 54 cases of GCA (RR 2. 1 cases/1 000 000 persons) have been reported. The nationwide survey allowed the characterization of 60 PMR and 35 GCA cases. Median time to the onset of first symptoms was 10 (range 2-30) and 7 (range 2-25) days for PMR and GCA, respectively. Phenotype, GCA-related ischemic complications and -large vessel vasculitis as well as therapeutic management and follow-up seemed similar according to the number of vaccine shots received and when compared to the literature data of unvaccinated population. Although rare, the short time between immunization and the onset of first symptoms of PMR and GCA suggests a temporal association. Physician should be aware of this potential vaccine-related phenomenon.